2016
DOI: 10.1155/2016/8178901
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Contamination Characteristics and Health Risks Assessment ofCommelina africanaL. and Psammitic Sandflats in the Niger Delta, Nigeria

Abstract: The purpose of this study was to investigate and quantify trace metal concentrations in Commelina africana L. and psammitic sandflats from an intertidal coastal ecosystem in Niger Delta, Nigeria, and to evaluate their spatial distribution, degree of contamination, and source apportionment. The environmental risks associated with soil contamination were elaborately assessed using potential ecological risk index, sediment quality guidelines, and enrichment relative to background levels. The mean concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The following pollution indices were adopted to estimate heavy metal pollution of sediment samples obtained from the study area: (i) degree of contamination (CD) (ii) contamination factor (CF) (iii) pollution index (PI) (iv) geoaccumulation index (I geo ) Contamination degree is estimated to give a holistic impact of multimetals on the environment [12,13]. In this study CD was calculated using the formula developed by Hakanson [14], which states that CD is the sum total of CF of the individual metals CD = ∑ CF Where n corresponds to the number of metals and CF n is the contamination factor of metal n. PLI is categorized as follows: background concentration (PLI = 0), unpolluted (0 < PLI ≤ 1), unpolluted to moderately polluted (1 < PLI ≤ 2), moderately polluted (2 < PLI ≤ 3), moderately to highly polluted (3 < PLI ≤ 4), highly polluted (4 < PLI ≤ 5) and very highly polluted (PLI > 5).…”
Section: Sediment Pollution Indices and Ecological Risk Assessmentmentioning
confidence: 99%
“…The following pollution indices were adopted to estimate heavy metal pollution of sediment samples obtained from the study area: (i) degree of contamination (CD) (ii) contamination factor (CF) (iii) pollution index (PI) (iv) geoaccumulation index (I geo ) Contamination degree is estimated to give a holistic impact of multimetals on the environment [12,13]. In this study CD was calculated using the formula developed by Hakanson [14], which states that CD is the sum total of CF of the individual metals CD = ∑ CF Where n corresponds to the number of metals and CF n is the contamination factor of metal n. PLI is categorized as follows: background concentration (PLI = 0), unpolluted (0 < PLI ≤ 1), unpolluted to moderately polluted (1 < PLI ≤ 2), moderately polluted (2 < PLI ≤ 3), moderately to highly polluted (3 < PLI ≤ 4), highly polluted (4 < PLI ≤ 5) and very highly polluted (PLI > 5).…”
Section: Sediment Pollution Indices and Ecological Risk Assessmentmentioning
confidence: 99%
“…However, the Igeo of Cd ranged from 31.13 -41.52 which is an indication of extreme contamination. The results of geoaccumulation index in previous studies carried out within Niger Delta byNsikak et al (2016),Aigberua et al (2017),Okoye et al (2021),Aigberua (2021), and Tubotu and Agbaire (2022) indicate that Ni, Pb, Cr and As had values <1. This implies that the sites studied were uncontaminated by these heavy metals.…”
mentioning
confidence: 80%
“…This implies that the sites studied were uncontaminated by these heavy metals. However,Aniekan et al (2014),Nsikak et al (2016),Nwankwoala andEmemu (2018), and Tubotu and Agbaire (2022) found in their separate studies that Cd had Igeo values ranging between 1.69 and 5.07. This implies a range of moderate to extreme contamination.…”
mentioning
confidence: 97%
“…Ecological risk potential index (RI) represents the overall ecological risk of different heavy metals in soil, assesses the likely degree of contamination by trace metals taking into account the relative toxicity of the metals in general and the short and long term response of the environment [Benson et al 2016;Hakanson 1980]. This risk index evaluates the harmful effect of heavy metals in soils, and was calculated through equations 6 and 7:…”
Section: Evaluation Of the Potential Ecological Risk Due To Heavy Met...mentioning
confidence: 99%
“…(7) (7) Where Ri is the index of the ecological risk potential of an individual metal i, Tri represents the toxicological response factor of metal i, which reflects the level of toxicity and sensitivity of organisms to the metal and CFi is the contamination factor of metal i. The toxicological response factors for As, Cd, Pb, Cu, Cr, Fe and Zn are 10, 30, 5, 5, 2, 1 and 1 respectively [Bhatti et The potential ecological risk factor associated with an individual metal (ERi) was categorized as: low risk (ERi<40), moderate risk (40≤ERi<80), considerable risk (80≤ERi<160), high risk (160≤ERi<320) and very high risk (ERi≥320).…”
Section: Evaluation Of the Potential Ecological Risk Due To Heavy Met...mentioning
confidence: 99%